FAMILY MANAGEMENT OF PATIENTS TREATED IN THE INTENSIVE CARE UNIT : A LITERATURE STUDY: MANAJEMEN CEMAS KELUARGA PASIEN YANG DIRAWAT DI RUANG INTENSIVE CARE UNIT : SEBUAH STUDI LITERATUR - Afifah Ayu Syaiful (JURNAL KEPERAWATAN, 2023)
Anxiety can appear automatically due to excessive stimuli both internally and externally so that it exceeds the individual's ability to cope. The impact of anxiety will affect the mind and motivation so that the family is not able to develop roles and functions that are supportive of the healing process and recovery of family members who are being treated in the Intensive Care Unit (ICU). The purpose of this literature study is to understand the management of anxiety in the family of patients treated in the ICU. The method used in this study was a literature review with electronic searches on 3 online databases, namely: Google Scholar, PubMed and Portal Garuda. The keywords used were "management", "family anxiety" and "intensive care unit". The criteria for the articles selected in this review were full text, published in 2017-2021. The results of the search and assessment obtained as many as 50 articles which were then carried out by data extraction on 5 articles. The results showed that what nurses can do in managing anxiety in the families of patients treated in the ICU were controlling family stress, health education, therapeutic communication and spirituality guidance.